Promoting Interventions to Develop Religous Identity of Secondary School Students - Prawitasari, Galuh; Suwarjo, Suwarjo (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
Adolescence is known as the transition from childhood to adulthood. In this period, the adolescent will experience many changes related to their identities in various domains of life, including the religious domain. This study aims to investigate the profiles of religious identity status of early adolescents. A total of 116 secondary school students participated in this study. Data were collected by using the Scale of Religious Identity Status. The results showed that students’ religious identity status were distributed in four categories: achievement (66%), searching moratorium (23%), foreclosure (10%), and moratorium (1%). Implications for guidance and counseling services in secondary school are discussed to promote the development of religious identity of early adolescents.